Numerical Renormalization Group computation of temperature dependent specific heat for a two-channel Anderson model - Ferreira, J. V.B.; Ferreira, A. I.I.; Leite, A. H.; Líbero, V. L. [UNESP] (Elsevier, 2012)
The Numerical Renormalization Group (NRG) is applied to diagonalize a two-channel Anderson model describing a local magnetic impurity embedded in a fermionic bath. In spite of the difficulty in computing the specific heat using NRG, the interleaving discretization and multi-step iterative transformation virtually eliminate the numerical oscillations introduced by the logarithmic discretization of the conduction band. These allow to cover uniformly a large range of temperature, from the top of the band to a very small fraction of the bandwidth. This is relevant in describing, for instance, the presence of a low temperature Kondo resonance together with a high temperature Schottky peak, as well to cover Fermi and non-Fermi liquid regimes, like in the recent studied Ce1 -x LaxNi9Ge4 family. We highlight the importance in describing the Schottky peak to define the number of degrees of freedom of the local levels, in order to correctly define the model to describe a given compound. © 2011 Elsevier B.V. All rights reserved.
Keywords: Heavy fermion; Kondo effect; Local moment in compound and alloy; Multi-channel Anderson model; Numerical Renormalization Group; Specific heat; Theories and models of many electron systems